Effects of Two Modes of Computer Assisted Instruction on Pupils’ Achievement and Retention in English Language Spelling in Niger State Nigeria (International Journal of Innovative Research in Computer Science & Technology, 2020)
The study investigated the effects of two  modes of Computer Assisted Tutorial, Drill and Practice  Instructional packages (CAI) on Pupils Achievement and  Retention in English Language Spelling in Niger State. Findings show that CAI Tutorial, drill and practice  packages mode strategy of instruction enhanced  achievement and retention of English language spelling.  The study adopted quasi–experimental design. Purposive  sampling was used to select six schools from the seven  educational zones in Niger State. The study sample  comprised of 87 males and 93 females. Experimental  groups were taught with CAI Tutorial, Drill and Practice  packages while Control group was taught with lecture  method. Six research questions and six hypotheses guided  the study. English Language Achievement Test (ELAT)  was used for data collection. The CAI packages and ELAT  were face validated by experts while the reliability was  established using Kuder Richardson (KR 20) analysis and  the reliability coefficient was found to be r = 0.74. Mean  and standard deviation were used to analyze the research  questions while analysis of covariance (ANCOVA) was  used in the testing of the hypotheses. It is recommended  that, curriculum planners should infuse CAI packages into  English language programmes so that primary school  teachers’ can use it to teach English language concepts.
Keywords: Achievement; CAI modes; Effects; English; Language Spelling; Retention.